Sociocultural correlates of eating pathology in college women from US and Iran - Sahlan, Reza N.; Akoury, Liya M.; Habashy, Jessica; Culbert, Kristen M.; Warren, Cortney S. (Frontiers in Psychology, 2022)
Objective The buffering role of the hijab as a protective factor against eating pathology has been questioned in countries where wearing the hijab is compulsory, such as Iran; and, cross-cultural comparisons of body image in Iranian and Western women are sparse. Consequently, we examined sociocultural correlates of eating pathology in US and Iranian women. Method College women from the US (n = 709) and Iran (n = 331) completed the Eating Disorder Examination-Questionnaire (EDE-Q) and the Sociocultural Attitude Toward to Appearance Questionnaire-4 (SATAQ-4). Prior to examining main hypotheses, we evaluated whether the scales perform similarly (i.e., establish measurement invariance) by culture. Results The EDE-Q and SATAQ-4 were not invariant by culture indicating that the scales performed differently across groups, so separate analyses were conducted in each sample. Thin-ideal internalization and pressures for thinness were significant positive predictors of eating pathology in both US and Iranian women. Conclusion Both pressures for thinness and thin-ideal internalization appear to be relevant to eating pathology in women from both cultures. However, there may be important cross-cultural differences in the interpretation or experience of these constructs. Further understanding of this measurement non-invariance and the ways in which Iranian women may be uniquely impacted by Western values of appearance is a critical next step.